Implication of types of feeds combined goat manure for preference black soldier fly (BSF) : Hermetia illucens L. Issue 2 (July 2021) - Indri, I; Sjam, S; Gassa, A; Dewi, V S
Abstract: Hermetia illucens L. (Diptera: Stratiomydae ) called black soldier fly (BSF) has an important role in the degradation of organic waste or bioconversion activity. The current study compared some types of feeds to preference BSF to eggs laid and the implication of the number of larvae and the size of pupae produced, the percentage of larvae that became adults. Type of feeds is rice bran, mixture of fruits waste, agricultural waste, vegetable waste and household waste. The type of feeds mixed with goat mature. The study reports that Black Soldier Fly (BSF) produced the hightest number of egg colonies in household waste (6 colonies) then vegetable waste (5 colonies), bran (4.3 colonies), fruits waste (3.3 colonies) and the lowest on agricultural waste (1 coloni). The highest number of larvae was in bran (4783), then household waste (1942), vegetable waste (1511), fruits waste (983) and the lowest in agricultural waste (276). The longest pupa size is in fruits waste (2 cm), household waste (1.96 cm), vegetable waste 1, 84 cm), bran (1.51 cm), and the lowest is in agricultural waste (1.46). the highest number of imago was in the bran (2266 heads), vegetable waste (396 heads), fruits waste (95 heads), agricultural waste (674.3 heads) and the lowest was in household waste (661.3 heads)